Ethnic Identity: A Psychoanalytic Critique - Bloom, Leonard (PINS-Psychology in Society, 2026)
In this paper I examine ethnicity and identity-formation in South Africa. I use psychoanalytic theories of some pathological aspects of narcissism to interpret how ethnic identity is an attempt to defend the self against feelings of vulnerability and inferiority that are concealed by manifest aggressive and assertive social behaviour. It is claimed that the intensity and persistence of ethnicity in South Africa is one of the results of racist ideologies and practices, and it is therefore implied that as racism is abated so will the intensity of ethnicity diminish.